Introduction to Programming with Fortran with coverage of Fortran 90, 95, 2003 and 77 - Chivers, Ian; Sleightholme, Jane (Springer London : Imprint: Springer, 2006)
Introduction to Programming with Fortran contains: lots of clear and simple examples highlighting the key language features of the most recent versions of Fortran - Fortran 2003, 95 and 90. practical examples based on ISO TR 15580 and ISO TR 15581 which are widely supported and cover the ISO TR on Enhanced Modules - particularly important to large code suites common problems that occur when programming which are highlighted via clear examples and solutions Introduction to Programming with Fortran is an essential introduction for beginners as well as a concise reference for professionals. Overall the book gives a very effective hands-on coverage of Fortran, valuable to students and practitioners alike. Ian Chivers and Jane Sleightholme are the joint owners of comp-fortran-90, which is a lively forum for the exchange of technical details of the Fortran language. Both authors have been involved in teaching and supporting Fortran and related areas for over 20 years and their latest book reflects the lessons that have been learnt from their experience with Fortran over the last few years.